Mobile application design for protecting the data in cloud using enhanced technique of encryption - Sakinah Ali Pitchay; Farida Hazwani Mohd Ridzuan; Alhiagem W.A.A.; Perumal S. (Science Publishing Corporation Inc, 2024)
Indexed by SCOPUS/ERA